POLA PERTUMBUHAN DAN FAKTOR KONDISI KERANG BULU (Anadara pilula) DI PERAIRAN DESA KALIREJO, PASURUAN, JAWA TIMUR - Yovicta Anastasya Nadin; Dony Prasetyo; Hariyadi Hariyadi (Universitas Muhammadiyah Malang, 2025)
One species of the genus Anadara, used as an alternative food source, is the fur shells (Anadara pilula). The purpose of this research is to analyze the growth pattern, condition factor, and the condition index of fur shells (Anadara pilula) in the waters of Kalirejo village, Pasuruan East Java. This research was conducted for three months. Samples of fur shells used as much as 200 each month. Long relationship weight is analyzed using regression analysis. The results showed that the value of B < 3 indicated a negative alometry growth pattern. The value of condition factor in each month is 1.040026, 1.044695, and 1.070018926, this indicates that fur shells have a less flat body shape. As for the value of the condition index in each month, namely 0.334421, 0.512482, and 0.34303959, it indicates that the shell condition index feathers have a value of < 2.5 which means the fur shells belong to the skinny category. Condition factor values and condition indices can be influenced by factors such as Reproduki process, environmental condition, and food availability.